2001
DOI: 10.1002/ps.363
|View full text |Cite
|
Sign up to set email alerts
|

Chitin synthesis and inhibition: a revisit

Abstract: Chitin is an abundant biologically important aminopolysaccharide composed of N-acetyl-D-glucosamine units. Individual polymers, which are synthesized intracellularly by chitin synthase (CS), a membrane-bound glycosyl transferase, are translocated across the plasma membrane and coalesce to form rigid crystallites. These crystallites, inter alia, are integral parts of septa and cell walls in yeast and filamentous fungi, respectively, and of cuticles in invertebrates, notably crustaceans and insects. Despite deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 29 publications
3
163
0
6
Order By: Relevance
“…This includes trehazolin and allosamidin, two pseudo-saccharides, which are both inhibitors of key enzymes involved in chitin synthesis [148][149][150]. While both trehazolin and allosamidin are effective in vitro, the large number of hydroxy groups in the molecules prevent them penetrating the insect cuticle and reaching their specific targets [151] and this has limited their utilisation for in vivo pest control.…”
Section: Chitin Synthase Disruption By Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes trehazolin and allosamidin, two pseudo-saccharides, which are both inhibitors of key enzymes involved in chitin synthesis [148][149][150]. While both trehazolin and allosamidin are effective in vitro, the large number of hydroxy groups in the molecules prevent them penetrating the insect cuticle and reaching their specific targets [151] and this has limited their utilisation for in vivo pest control.…”
Section: Chitin Synthase Disruption By Pesticidesmentioning
confidence: 99%
“…As chitin is not a biopolymer in vertebrates and is consumed regularly in the human diet, it is considered safe for the control of chitinous pests [149]. Unfortunately there is dearth of information regarding the toxicity of chitin/chitosan to beneficial microbes, nematodes or insects other than those purposely applied as biological control agents alongside chitin products, including saprotrophic/nectrophic organisms.…”
Section: Human/animal Toxicity Of Chitin and Chitosanmentioning
confidence: 99%
“…Previous studies that have attempted to elucidate the exact mechanism behind the action of benzoylphenylureas gave rise to speculations about their involvement in other pathways. They may affect not only the chitin biosynthesis events (COHEN, 2001), but also others processes, as the inhibition of the glucose conversion into fructose-6-phosphate (PALLI & RETNAKARAN, 1999), an important step known in glycolysis too (NELSON & COX, 2011). However, whether these compounds produced potential consequences to other metabolic pathways involving glucose in ticks (and potential mechanisms of action governing them) had not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether these compounds produced potential consequences to other metabolic pathways involving glucose in ticks (and potential mechanisms of action governing them) had not yet been confirmed. Cohen (2001) stated that fluazuron inhibits glucose phosphorylation process. In accordance to his results, our findings suggested that an imbalance in glucose homeostasis occurs due to the previous inhibition of chitin synthase caused by fluazuron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation